Deskripsi Tingkat Pengetahuan Guru dan Orang Tua Tentang Bullying Pada Anak Usia Prasekolah - Puspitasari, Tarissa Widhi; Diahsari, Armenia; Rahmadewi, Triani (REAL in Nursing Journal, 2024)
Background: Bullying is an aggressive behavior that is deliberately carried out by a person or group to hurt physically or emotionally repeatedly. Preschool education is given to build children’s characters who are still difficult to socialize and control emotions. The phenomenon of bullying was found in the environment of preschool children which was considered a normal thing by teachers and parents of students. To determine the level of knowledge of teachers and parents about bullying behavior in preschool children. Methods: This study is a quantitative descriptive study with a cross-sectional approach. Samples were taken from 10 kindergartens in the Banyuraden Village area. The teacher sampling technique used total sampling with 39 samples and parents used simple random sampling with 208 samples. The research instrument used a questionnaire. Results: The results of the study showed that most teachers and parents had a good level of knowledge about bullying in preschool children, but many parents still considered that habituating children's behavior at home did not have an impact on the formation of bullying behavior. Conclusion: Teachers and parents have an important role in avoiding the formation of the character of bullies as early as possible so that knowledge about bullying must be possessed. Researches with different methods can be carried out for more valid results